Kajian Pengembangan Ekowisata Bahari Sebagai Mata Pencaharian Alternatif Bagi Masyarakat Tulamben dan Amed Kabupaten Karangasem Propinsi Bali - I Gede Made Subagiana; Sagung Mas Suryaniadi; Ni Luh Made Wijayati (Jurnal Bisnis dan Kewirausahaan, 2019)
Developing marine eco-tourism as an alternative source of livelihood. To accelerate poverty alleviation in Karangasem regency, where 6.88% of the population of 27,800 people are classified as poor , various efforts have been made by the Regional Government such as developing marine eco-tourism in Tulamben Village, Kubu Sub-district and Amed Village, Abang District of Karangasem Regency. Developing of marine eco-tourism resulted in a shift in livelihood patterns of the population from the agricultural sector to the tourism industry sector. The problem in this research is "Is Marine Eco-tourism Development feasible to be an alternative livelihood for Tulamben and Amed people of Karangasem Regency?" The research objectives are to assess whether marine eco-tourism development is a viable alternative livelihood for Tulamben and Amed communities. The method used is the Contingent Valuation Method: Willingness to Accept (WTA), Willingness to Pay (WTP) and Economic Potential Analysis and SWOT analysis. Result: the Contingent Valuation Method shows WTP value of Rp.176.500 higher than WTA value of Rp.154.500. Analysis of Economic Potential, from analysis of the economic potential of Marine Ecotourism, can create value Rp.4.728.964.500 from every tourist visit to an object. From the above two analyses, it can be concluded that Marine Ecotourism is very feasible as an alternative livelihood. To complement the analysis of marine eco-tourism development strategy with SWOT, it can be recommended as follows:• Improving cooperation with domestic and foreign travel agents• Providing an information center related to Marine Ecotourism activities.• Increasing safety insurance for tourists• Improving the quality of human resources, through on-going training. Pengembangan Ekowisata Bahari sebagai Mata pencahariaan alternatif. Untuk mempercepat pengentasan kemiskinan di Kabupaten Karangasem, dimana 6,88% dari jumlah penduduknya tergolong miskin. Menyadari akan hal ini berbagai upaya telah dilakukan oleh Pemerintah Daerah diantaranya adalah Pengembangan Ekowisata Bahari di Desa Tulamben, Kecamatan Kubu dan Desa Amed Kecamatan Abang, Kabupaten Karangasem. Dengan berkembangnya Ekowisata Bahari mengakibatkan adanya pergeseran pola mata pencaharian penduduk dari sektor pertanian ke sektor industri pariwisata. Yang menjadi masalah dalam penelitian ini adalah Apakah Pengembangan Ekowisata Bahari layak untuk dijadikan mata pencaharian Alternatf bagi Masyarakat Tulamben dan Amed Kabupaten Karangasem? Tujuan Penelitian: Untuk mengkaji apakah Pengembangan Ekowisata Bahari layak dijadikan sebagai mata pencaharian alternatif bagi masyarakat Tulamben dan Amed. Metode Penelitian. Metode yang digunakan adalah Metode Kontingen (Contingen Valuation Method): Willingness to Accept (WTA), Willingness to Pay (WTP).dan analisis Potensi Ekonomi serta analisis SWOT. Hasil kajian menunjukkan nilai WTP lebih tinggi dari nilai WTA berarti Ekowisata Bahari layak sebagai mata pencaharian alternatif.